2006
DOI: 10.1096/fj.06-6710com
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory uptake of manganese requires DMT1 and is enhanced by anemia

Abstract: Manganese, an essential nutrient, can also elicit toxicity in the central nervous system (CNS). The route of exposure strongly influences the potential neurotoxicity of manganese-containing compounds. Recent studies suggest that inhaled manganese can enter the rat brain through the olfactory system, but little is known about the molecular factors involved. Divalent metal transporter-1 (DMT1) is the major transporter responsible for intestinal iron absorption and its expression is regulated by body iron status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
129
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 57 publications
3
129
1
1
Order By: Relevance
“…Immunostaining studies suggest that DMT1 expression is strongest at the brush border of the apical pole of the enterocytes, which is consistent with the role for DMT1 in luminal metal uptake . Moreover, recent immunohistochemical experiments revealed that DMT1 is also expressed in the lumen microvilli and end-feet of the sustentacular cells of the olfactory epithelium, suggesting an alternative route of metal exposure (Thompson et al, 2007). In macrophages, DMT1 is restricted in the phagosomal membrane where red cells are engulfed.…”
Section: Dmt1 Localizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Immunostaining studies suggest that DMT1 expression is strongest at the brush border of the apical pole of the enterocytes, which is consistent with the role for DMT1 in luminal metal uptake . Moreover, recent immunohistochemical experiments revealed that DMT1 is also expressed in the lumen microvilli and end-feet of the sustentacular cells of the olfactory epithelium, suggesting an alternative route of metal exposure (Thompson et al, 2007). In macrophages, DMT1 is restricted in the phagosomal membrane where red cells are engulfed.…”
Section: Dmt1 Localizationmentioning
confidence: 99%
“…Mn toxicity from dietary intake is rare; its uptake is tightly regulated, and any excess of ingested Mn is readily excreted via the bile. In contrast, both pulmonary uptake and particulate transport via the olfactory bulb (Saric, 1986;Aschner et al, 1991;Thompson et al, 2007) can lead to deposition of Mn within the striatum and cerebellum and inflammation of the nasal epithelium .Mn plays an important role in the development and functioning of the brain (Prohaska, 1987;Takeda, 2003). Mn deficiency may result in birth defects, poor bone formation and an increased susceptibility to seizures (Aschner, 2000;Aschner et al, 2002).…”
mentioning
confidence: 99%
See 3 more Smart Citations